2014
DOI: 10.1186/1742-4755-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for perinatal death in two different levels of care: a case–control study

Abstract: BackgroundAccording to the World Health Organization, there are over 6.3 million perinatal deaths (PND) a year worldwide. Identifying the factors associated with PND is very helpful in building strategies to improve the care provided to mothers and their babies.ObjectiveTo investigate the maternal, gestational and neonatal factors associated with PND at two different levels of care.MethodsCase–control study including 299 PND cases and 1161 infants that survived the early neonatal period (controls) between 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…Male neonates had higher odds of death compared to female neonates, which agree with previous findings from both developed and developing countries [ 8 , 11 , 18 20 , 36 , 37 ]. This could be due to the fact that neonatal period is the time at which innate biological differences between males and females are prominent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Male neonates had higher odds of death compared to female neonates, which agree with previous findings from both developed and developing countries [ 8 , 11 , 18 20 , 36 , 37 ]. This could be due to the fact that neonatal period is the time at which innate biological differences between males and females are prominent.…”
Section: Discussionsupporting
confidence: 91%
“…Bivariate and multivariate analyses were done using binary logistic regression model to examine determinants of neonatal mortality. Bivariate analysis was done first and then followed by multivariate analysis, as in previous studies [ 19 , 20 ]. The bivariate analysis was done to examine the odds of exposure difference between cases and controls, and unadjusted odds ratios with 95% confidence interval were calculated for all variables included in the bivariate model.…”
Section: Methodsmentioning
confidence: 99%
“…Another research in Bali, Indonesia, using the case control method on 47 women as the cases and 47 women as the controls found that the presence of Asphyxia neonatorum in infants posed a risk of 2,270 timesgreater to the perinatal mortality than in infants without asphyxia neonatorum [4]. Another research that is in line with this research is asphyxia had a risk of 5.3 times to perinatal death [5].…”
Section: The Risk Of Asphyxia To Perinatal Deathsupporting
confidence: 54%
“…The latter was contrary to results from a 2014 study conducted in India. The authors found that married egalitarian gender attitudes and gender sensitive decision making, meaning that the wife takes part in the decision on issues that affect her or her family, among married men were both associated with current contraceptive use [ 11 ]. There is no consensus regarding associations between gender attitudes and contraception use in all low- and middle-income countries and research should be performed at country level to account for local culture.…”
Section: Introductionmentioning
confidence: 99%